Desa Berdaya, Anggaran Terjaga: Sosialisasi Anti-Fraud dan Akuntabilitas Dana Desa di Negeri Tamilouw Kecamatan Amahai, Kabupaten Maluku Tengah - Wahab Tuanaya; Jusuf Madubun; Muhtar (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
The Community Service Program “Empowered Village, Secure Budget” in Tamilouw Village aims to strengthen integrity-based Village Fund governance through anti-fraud outreach, practical mentoring, and social accountability. The design includes initial diagnostics, interactive training (fraud triangle, role separation, three-way match), case clinics and internal audit simulations, and pre-post evaluations and citizen feedback using a community scorecard. Mixed methods were used to assess changes in knowledge, work behavior, and documentation quality. Results showed an increase in knowledge from 62% (pre) to 87% (post) with a normalized gain of 0.66 (high category), adoption of an internal control checklist by 80% of participants, and a 32% decrease in recording errors. Public transparency increased: the proportion of residents aware of Village Fund allocations rose from 15% to 68%, while a scorecard pilot in two hamlets resulted in an average satisfaction rating of 84% along with measurable improvement plans. The integration of ethical values ​​was strengthened through a civil servant code of ethics, a whistleblowing channel, and the establishment of an ethics team and community audit. 93% of participants agreed that integrity is a key performance indicator. The findings confirm that the combination of risk-based controls, consistent data publication, and meaningful participation effectively reduces opportunities for irregularities while enhancing village government legitimacy. This model is worthy of replication as a prototype for coastal integrity villages in eastern Indonesia. Further quarterly mentoring support is recommended.